Segmentacija trga in spremembe na področju nizkocenovnih hotelov na mestnih območjih Južnoafriške republike - Rogerson, Jayne M. (Urbani izziv, 2013)
Market segmentation is a critical driver of change in the hotel industry, resulting in the appearance of differentiated forms of hotel property developments, including budget hotels. International research on budget hotels is mainly limited to North America and Europe, with some more recent studies on emerging economies. This article examines the role of budget hotels within the wider restructuring of the South African hotel industry following the country's re-entry into the global tourism economy after its democratic transition. Historically, the South African hotel industry became dominated by one- and two-star budget accommodation as a result of the country's liquor legislation. With the reconfiguration of the hotel industry after 1990 to target the growing international tourism market, the role of budget hotels changed. This analysis examines the diminished role of budget hotels in South Africa's hotel economy, the shifting nature of the budget hotel and location patterns of budget hotels from 1990 to the present. It shows that post-1990 budget hotels are mainly concentrated in large cities andsecondary centres of South Africa, and that in small towns the former liquor-focused budget hotel has been replaced by other forms of accommodation.
Keywords: cene; hoteli; hotelirstvo; Južnoafriška republika; mesta